Keratopigmentation in the modern era: A review of current techniques, results, and safety - Kepa Balparda; Mauricio Agudelo-Cardona; Francis Ferrari; Tatiana Herrera-Chalarca; Isabela Franco-Sánchez (Indian Journal of Ophthalmology)
To conduct a literature review on current knowledge regarding keratopigmentation (KTP), with a particular focus on femtosecond-assisted procedures. A narrative literature review was performed. Academic databases (PubMed, Google Scholar, Cochrane Library, and SciELO) were searched for articles containing the keywords “keratopigmentation” and “corneal tattoo.” All relevant articles were reviewed, and appropriate ones related to the topic were included in the review. KTP has a variety of indications, including enhancing the aesthetic profile of blind eyes with decompensated corneas and alleviating symptoms related to iris atrophy. The trend of strictly cosmetic KTP has recently gained popularity among several surgeons worldwide. Despite some controversy, most articles reported excellent outcomes associated with KTP, alongside a high safety profile. Histopathological studies have demonstrated that modern micronized pigments are entirely biocompatible. Femtosecond laser-assisted KTP appears to be a safe and effective procedure. However, more long-term studies are necessary to enhance our understanding of the risks associated with strictly cosmetic applications of this technique.